Framtidens mångfald : Hur når vi nya vägar till en berikande organisation - Westbom, Ade (2012)
The aim of this thesis was to investigate the potential problems hindering the implementation of diversity initiatives at Luleå municipality and to find out which strategies are adopted by municipality leaders to promote diversity within the municipality. Interviews were conducted with nine employees from different areas within the municipality with a focus on the knowledge of the current initiatives on gender and ethnicity/cultural diversity. The results indicated possibilities for improvement of diversity initiatives. All respondents reported that they had sufficient knowledge about discrimination and diversity, which give positive impacts on the organization. Luleå municipality had established a common goal on diversity initiatives within the organization. From the results it was found that taken measures did not seem to lead to apparent improvement. The possible reasons could be the low male applicants for a job in the municipality or that discrimination toward specific groups exist. Therefore, it can be concluded that Luleå municipality needs to put more efforts in implementing their vision on the diversity initiatives and the positive outcome will depend on the enthusiasm and the dedicated time of the municipality leaders. The municipality leaders were aware of the diversity issues, however, due to the high demand of day-to-day operations, the priority for these issues are kept low. Validerat; 20120827 (anonymous)